Processed bed elevation picks from airborne radar depth sounding over the Jutulstraumen rift area (2001/02 season) ... - Ferraccioli, Fausto; Jones, P.; Curtis, Michael; Leat, Philip; Riley, Teal (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
A British Antarctic Survey Twin Otter and survey team acquired 15,500 line-km of aerogeophysical data during the 2001/02 Antarctic field season along a 1-km line spacing grid with tie-lines 8 km apart. Twenty-five flights were flown from the South African base SANAE, for a total of 100 survey hours. We present here the processed bed elevation picks from airborne radar depth sounding. The airborne-radio echosounding data were collected for 5 flights, to image ice-thickness and bedrock configuration. Data are provided as XYZ ASCII line data. This high-resolution aerogeophysical survey was part of the "Magmatism as a Monitor of Gondwanabreak-up" project (MAMOG) of the British Antarctic Survey, which included new geochemical investigations, structural geology, geochronology, and AMS studies over western Dronning Maud Land. ... : Radar data presented in Ferraccioli et al (2005). Data collected by BAS used the PASIN radar echo sounding system (table 1 (Corr et al., 2007)). Data provided here includes picked ice sheet bed elevation along exploratory or longer transit lines. No radar data was collected from the main survey grid. Channel description: Basic Channels Name Description Lon Longitude WGS 1984 Lat Latitude WGS 1984 x x projected meters* y y projected meters* Radar surfElev Surface elevation. BEDMAP2 surface used here. (m) bedElev Ice bed elevation, derived by subtracting tice from surfElev (m) tIce Ice thickness (m). *Projected coordinates (x and y) are in Lambert conic conformal with two standard parallels defined as follows: Latitude of natural origin: -71 Longitude of natural origin: 0 Scale factor at natural origin -75.33333333333 False easting 0 False northing 2082760.109 ...